2009
DOI: 10.1063/1.3147702
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of the interstellar isomerization reaction HOC+→HCO+ catalyzed by H2: New Insights from the reaction electronic flux

Abstract: A theoretical study of the mechanism of the isomerization reaction HOC(+) --> HCO(+) is presented. The mechanism was studied in terms of reaction force, chemical potential, reaction electronic flux (REF), and bond orders. It has been found that the evolution of changes in REF along the intrinsic reaction coordinate can be explained in terms of bond orders. The energetic lowering of the hydrogen assisted (catalyzed) reaction has been identified as being due to the stabilization of the H(3)(+) transition state c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 35 publications
2
76
0
Order By: Relevance
“…It has been shown that the REF is useful in identifying electronic activity within the reaction regions along the reaction coordinate [21,23,24], in this context dipole moment and natural charge are complementary quantities. By observing the DM profiles, it is possible to conclude some features about the nature of the REF.…”
Section: Dipole Moments and Bond Ordersmentioning
confidence: 99%
“…It has been shown that the REF is useful in identifying electronic activity within the reaction regions along the reaction coordinate [21,23,24], in this context dipole moment and natural charge are complementary quantities. By observing the DM profiles, it is possible to conclude some features about the nature of the REF.…”
Section: Dipole Moments and Bond Ordersmentioning
confidence: 99%
“…The reaction electronic flux also gives phenomenological insights on the electronic activity taking place during a chemical reaction by rationalizing the electronic activity in terms of polarization and electronic transfer contributions J p and J t [14][15][16][17][18]30]:…”
Section: The Reaction Electronic Flux (Ref)mentioning
confidence: 99%
“…By evaluating μ along the reaction coordinate it is possible to determine the profile μ(ξ) that shows the evolution of the chemical potential during the chemical reaction. The reaction electronic flux (REF) associated to a chemical reaction is defined as [14][15][16][17][18]:…”
Section: The Reaction Electronic Flux (Ref)mentioning
confidence: 99%
“…HCO + + H 2 assisted (catalyzed) by dihydrogen which is proven to take place in interstellar medium [33,34]. This process is due to the stabilization of the H 3 + TS and the stepwise dissociation and formation of the H-O and H-C bonds, respectively.…”
Section: Introductionmentioning
confidence: 98%